ЗАРУБІЖНИЙ ДОСВІД ФУНКЦІОНУВАННЯ СВІТОВОЇ СИСТЕМИ ГАРАНТУВАННЯ ВКЛАДІВ: УРОКИ ДЛЯ УКРАЇНИ - Скірка, Андрій Сергійович (Науковий журнал «Світ фінансів», 2017)
Скірка А. С. Зарубіжний досвід функціонування світової системи гарантування вкладів: уроки для України. Розглянуто класифікацію систем гарантування вкладів. Досліджено історію функціонування системи страхування депозитів у США та наголошено про існування відповідальності власників за доведення до банкрутства банку. Проаналізовано головні аспекти функціонування страхування депозитів у Німеччині та Великобританії. Подано порівняльну характеристику основних аспектів законодавства про страхування вкладів у країнах ЄС та України. Обґрунтовано рекомендації стосовно вдосконалення вітчизняної системи гарантування вкладів та банківської системи загалом. Скирка А. С. Зарубежный опыт функционирования мировой системы гарантирования вкладов: уроки для Украины. Представлена классификация систем гарантирования вкладов. Исследована история функционирования системы страхования депозитов в США и отмечено существование ответственности за доведение до банкротства банка. Проанализированы основные аспекты функционирования страхования депозитов в Германии и Великобритании. Представлена сравнительная характеристика основных аспектов законодательства о страховании вкладов в странах ЕС и Украины. Обоснованы рекомендации по совершенствованию отечественной системы гарантирования вкладов и банковской системы в целом. Skirka A. International experience of the deposit guarantee system: lessons for Ukraine. Introduction. Economic growth is impossible without reliable and stable functioning of the banking system. In the current economic conditions the increase of public confidence in the banks, through the development of national deposit guarantee system are particularly relevant. The article presents the classification of deposit insurance system and also analyzed the existence of moral hazard in determining the size and facilities refund deposits. Purpose. The purpose of this paper is to analyze international experience of the deposit guarantee system and certain some aspects of the proceedings in Ukraine. Results. The article discusses the role of deposit insurance and the design features of deposit insurance systems in the world. It has been pointed some historical aspects of deposit insurance in the United States of America, also pointed about the existence of liability for proving to bankruptcy. The main aspects of deposit insurance in the Germany and United Kingdom are analysed. The mission of Financial Services Compensation Scheme in UK is to provide a responsive, well-understood and efficient compensation service for customers of financial services, which raises public confidence in the industry. Comparative description of the main aspects of legislation deposit insurance in the EU and Ukraine have been investigated. Special attention was paid to current condition of the global banking system and noticed the establishment Completing Europe’s Economic and Monetary Union and the European Deposit Insurance Scheme. Also mentioned about the crisis in Cyprus 2012-2013 years. Conclusion. The paper studies foreign experience of deposit insurance system and our recommendation was to improve our deposit guarantee scheme. Also National Bank must increase the effectiveness of banking supervision and monitoring of problem banks by dual supervision: from the NBU and the Deposit Guarantee Fund.